The effect of combined ultrasound stimulation and gastrodin on seizures in mice - Chen, Houminji; Miao, Yuqing; Duan, Haowen; Yi, Shasha; Lin, Zhengrong; Guo, Yanwu; Zou, Junjie; Niu, Lili (Frontiers in Neuroscience, 2024)
Both physiotherapy and medicine play essential roles in the treatment of epilepsy. The purpose of this research was to evaluate the efficacy of the combined therapy with focus ultrasound stimulation (FUS) and gastrodin (GTD) on seizures in a mouse model. Kainic acid-induced seizure mice were divided into five groups randomly: sham, FUS, saline + sham, GTD + sham and GTD + FUS. The results showed that combined therapy with ultrasound stimulation and gastrodin can significantly reduce the number and duration of seizures in GTD + FUS group. 9.4T magnetic resonance imaging and histologic staining results revealed the underlying mechanism of the combined therapy may be that ultrasound stimulation increases cell membrane permeability to increase GTD concentration in brain. In addition, we verified the safety of FUS combined with GTD therapy. This research provides a new strategy for neurological disorders combining treatment of physical neuromodulation and medicine.